A Review on Intestinal and Blood parasitic (Haemoparasite) protozoans - Said Muhammed Hussen (International Journal of Veterinary Science and Research - Peertechz Publications, 2020)
Parasites are a major cause of disease of man and domestic animals. More than half the human population lives in misery and pain and suffers vast economic losses due to parasites. Protozoa are ubiquitous throughout aqueous environments and the soil, and play an important role in their ecology. Optimal recovery and microscopic identification of protozoa from patients with intestinal infections is dependent on proper collection and preservation of fecal specimens. The most reliable way to diagnose a parasitic infection is by detection and identification of the infecting organism. All methods for the direct identification of parasites fail if the parasite density in the specimen is below the sensitivity of the method employed, or if the parasite cannot be directly demonstrated due to the life cycle in the host. In such cases indirect methods must be used. Ideally, serology should allow differentiation between recent and latent infections and should be able to demonstrate whether an animal is carriers as well as the elimination of the parasite after therapeutic measures have been applied.